Z historii etnomuzykologii w Galicji: pierwsze badania i publikacje melodii ludowych w XIX w. - Dowhaluk, Iryna (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
The history of studying and publishing Ukrainian and Polish folk melodies in Galicia traces back to the year 1822. In that year, Professor Karl Joseph von Hüttner [Karol Józef von (de) Hüttner] of the University of Lviv began publishing the calendar-almanac „Pielgrzym Lwowski” in Lviv. In its first issue, the publisher featured an article titled „Śpiewy ludu [wieyskiego]”, containing two Polish and two Ukrainian folk songs with melodies processed by Moroński. Karl Joseph von Hüttner’s initiative was later attempted to be continued by ethnographer, archivist Denis Zubrytskyi, and subsequently by public and political figure, journalist Ludwik Piątkewicz. Piątkewicz announced his intention to publish a collection of Polish and Ukrainian folk songs in the first issue of the monthly „Pątnik Narodowy”, which he founded and edited in 1827. In the journal, he also published an article titled „On Polish and Rus’ Folk Songs”, intended as a preface to the planned song collection. Karol Lipiński was invited to prepare the melodies for printing. However, the collection of folk songs was never published.